Modelling of Harbour and Coastal Structures - Karambas, Theophanis V.; Samaras, Achilleas (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As the most heavily populated areas in the world, coastal zones host the majority and some of the most important human settlements, infrastructures and economic activities. Harbour and coastal structures are essential to the above, facilitating the transport of people and goods through ports, and protecting low-lying areas against flooding and erosion. While these structures were previously based on relatively rigid concepts about service life, at present, the design-or the upgrading-of these structures should effectively proof them against future pressures, enhancing their resilience and long-term sustainability. This Special Issue brings together a versatile collection of articles on the modelling of harbour and coastal structures, covering a wide array of topics on the design of such structures through a study of their interactions with waves and coastal morphology, as well as their role in coastal protection and harbour design in present and future climates.